Knowledge, Attitudes, and Practices Toward COVID-19 Among Rural Residents of Hebei Province: A Cross-Sectional Survey. (13th October 2023) - Fang, Tingting; Li, Yanling; Jiang, Donghui; Liu, Lan; Fan, Fengning; Chen, Yuping; Zhao, Zihui
Abstract: Objective: Coronavirus disease (COVID-19) has spread worldwide due to high infectivity. The social sexual environment in rural areas of China and the weak basic medical facilities may affect the treatment and transmission of the disease. The aim of this study was to understand the knowledge, attitudes, and practices (KAP) related to COVID-19 among residents in rural areas experiencing the epidemic and the factors, to provide a basis for further epidemic prevention and control. Methods: The COVID-19 KAP of rural residents in Hebei Province was collected by the snowball sampling method. The COVID-19 KAP questionnaire was distributed on social platforms such as WeChat and QQ through a network questionnaire. Results: The overall level of COVID-19 KAP in rural residents was good, but in terms of knowledge, the correct rate of isolation was 73.2%, the correct rates of 2 disinfection items were 72.3% and 77.4%, and the correct rate of hand-washing was 70.7%; 54.5% residents felt panic; 81.0% disinfected household items; and 84.9% washed their hands correctly. Residents still needed to strengthen these aspects. A binary logistic analysis showed that age, education, and participation in training were factors affecting the level of COVID-19 KAP. Conclusions: This study found that rural residents had good levels of COVID-19 KAP, but there were gaps in specific issues that warrant attention. We advocate training on COVID-19 for rural residents.